2019
DOI: 10.7567/1347-4065/ab0ba5
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of longitudinal leaky surface acoustic wave propagation characteristics on a piezoelectric ScAlN layer/sapphire or quartz substrate

Abstract: Longitudinal leaky surface acoustic wave (LLSAW) modes with a high phase velocity are suitable for high-frequency SAW filter applications. However, their attenuation is higher than that of other SAW modes, causing a small Q factor. On the other hand, a low attenuation and high coupling factor K2 in LLSAWs on a piezoelectric thin plate/high-velocity sapphire or quartz substrate have been demonstrated theoretically and experimentally. We expected that LLSAWs propagating on a highly piezoelectric ScAlN layer/sapp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…Various SAW devices with ScAlN films/high phase velocity substrates have also been reported. [21][22][23][24][25][26][27] The K 2 for the 1st mode RSAW (=5.5%) on the IDT/ScAlN film/diamond substrate structure 21) was approximately 4.6 times higher than that for the IDT/AlN film/diamond substrate structure. The SAW on a polarity inverted ScAlN film structure was also studied for further enhancement of the K 2 for the 1st mode RSAW.…”
Section: Introductionmentioning
confidence: 90%
“…Various SAW devices with ScAlN films/high phase velocity substrates have also been reported. [21][22][23][24][25][26][27] The K 2 for the 1st mode RSAW (=5.5%) on the IDT/ScAlN film/diamond substrate structure 21) was approximately 4.6 times higher than that for the IDT/AlN film/diamond substrate structure. The SAW on a polarity inverted ScAlN film structure was also studied for further enhancement of the K 2 for the 1st mode RSAW.…”
Section: Introductionmentioning
confidence: 90%
“…Subsequently, various SAW devices using ScAlN film/high velocity substrate have been reported. [16][17][18][19][20] The K 2 of 5.5% in the Sezawa mode RSAW device of the IDT/ScAlN film/diamond substrate structure was approximately five times higher than that of the IDT/AlN film/diamond substrate structure. In addition, it has been theoretically found that the K 2 of the high-order mode RSAWs on wurtzite piezoelectric films/high velocity substrates can be further enhanced by using multilayer polarization reversal film structures.…”
Section: Introductionmentioning
confidence: 91%
“…Tetsuya Kimura, Masashi Omura 2018 Apply the inter-digital transducer cycle of 3.5 GHZ utilizing IHP SAW to another new SAW device LLSAW [ 70 ], and the results show that good transducer performance can still be obtained in the 5 GHZ range. In 2019, Masashi Suzuki and Naoya Sawada found that LLSAW propagating on a high-voltage electrical ScAlN layer/sapphire or quartz substrate also has high phase velocity, high K2, and low attenuation [ 71 ].…”
Section: Saw Filter Technologymentioning
confidence: 99%